2019
DOI: 10.1590/1806-9282.65.6.857
|View full text |Cite
|
Sign up to set email alerts
|

Reactional changes in short-term levonorgestrel-releasing intrauterine system (lng-ius) use

Abstract: SUMMARY OBJECTIVE: To evaluate endocervical and vaginal environment changes in women using a levonorgestrel-releasing intrauterine system (LNG-IUS). METHODS: A quasi-experimental study included sixty women who had an LNG-IUS inserted in the Family Planning Clinic of UNICAMP between April and November of 2016. Women in reproductive age, non-pregnant, without the use of antibiotics and contraceptives seeking for LNG-IUS insertion were selected for this study. All women were evaluated with regard to vaginal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
2
0
2
Order By: Relevance
“…As reported in literature various studies have been done to evaluate the effect of copper T as well as LNG IUCD on the vaginal health of women. 6,7,8,9,10,11,12,13,14,15,16 These studies have been enumerated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported in literature various studies have been done to evaluate the effect of copper T as well as LNG IUCD on the vaginal health of women. 6,7,8,9,10,11,12,13,14,15,16 These studies have been enumerated in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Literature does suggest that there is increase in prevalence of dysbiotic microbiome profile and raised cytokine profile after use of LNG IUCD. 8,9 There has been an observation of increased colonization of candida species after long term use as suggested by Donders et al and Lessard T et al Reactional changes in the vaginal environment have also been observed in a recent study by Giraldo et al 6,11,16 Few studies have reported a positive influence on the community stability with use of LNG IUCD but studies by Bassis et al and Jacobson et al found no evidence that LNG contraception altered the vaginal microbiota composition. 10,12,17…”
Section: Iucd and Vaginal Milieumentioning
confidence: 95%
“…(DE ALBUQUERQUE MARANHÃO, et al, 2019;BRANDÃO, et al, 2018). Em razão dos desconfortáveis sintomas, especialmente o prurido, muitas mulheres procuram exterminar fatores que possam intensificar esse desconforto, incluindo os COs, uma alternativa seria a utilização do sistema intrauterino liberador de levonorgestrel (SIU-LNG) um método contraceptivo eficiente que não provoca predisposição da candida, pelo contrário, um estudo constou que ocorre uma diminuição, pequena, mas existente da infecção por Candida sp após a inserção de SIU-LNG de curta duração (GIRALDO, 2019).…”
Section: Discussionunclassified
“…Dentre os efeitos colaterais mais frequentes estão às náuseas, fadiga, cefaleia, vômitos, dores abdominais, sangramento leve, menstruação irregular, disenteria, mamárias sensíveis, alterações no humor, sangramento fora do período menstrual, dentre outros (71) . O uso prolongado deste medicamento pode acarretar num aumento de desenvolver câncer de mama, câncer de colo e de vagina.…”
Section: Figura 8 -Pílulas Anticoncepcionais De Emergênciaunclassified